2002
DOI: 10.1046/j.1526-100x.2002.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Facilitation of Faunal Recruitment Benefit Ecosystem Restoration? An Experimental Study of Invertebrate Assemblages in Wetland Mesocosms

Abstract: We used wetland mesocosms (1) to experimentally assess whether inoculating a restored wetland site with vegetation/sediment plugs from a natural wetland would alter the development of invertebrate communities relative to unaided controls and (2) to determine if stocking of a poor invertebrate colonizer could further modify community development beyond that due to simple inoculation. After filling mesocosms with soil from a drained and cultivated former wetland and restoring comparable hydrology, mesocosms were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 22 publications
0
37
0
1
Order By: Relevance
“…Some studies conducted in invertebrates and vegetation have suggested the importance of this viable present egg bank to facilitate colonization after pond restoration (Brouwer and Roelofs, 2001;Brady et al, 2002;Jenkins and Boulton, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies conducted in invertebrates and vegetation have suggested the importance of this viable present egg bank to facilitate colonization after pond restoration (Brouwer and Roelofs, 2001;Brady et al, 2002;Jenkins and Boulton, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Macroinvertebrates are directly affected by the physical and chemical integrity of the surrounding environment, including water quality (EPA, 2002). They are known to influence the rates of nutrient cycling and decomposition, to have a central position in the wetland food webs and to integrate environmental impacts and changes through time (Scatolini and Zedler, 1996;Sharitz and Batzer, 1999;Brady et al, 2002;Stanczak and Keiper, 2004). Therefore, they are potentially useful as indicators of restoration success (Campbell et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Many aquatic beetles prefer breeding in waters with dense aquatic vegetation, as it provides food and cover for larvae and imagos (Hebauer 1986, De Szalay andResh 2000), as well as for other macroinvertebrate taxa (Nicolet et al 2004). The experiments of Brady et al (2002) confirm this hypothesis; they found similarities in invertebrate community structures between inoculated and natural water bodies and significant differences between inoculated and control areas without vegetation. However, the abundances of some groups, including Coleoptera, were much lower in the vegetated mesocosms of that investigation.…”
Section: Discussionmentioning
confidence: 78%
“…To facilitate the establishment of plant species to achieve a more natural habitat, it is a common procedure to inoculate desired plant species (Brady et al 2002). Breeding habits of aquatic beetles seem to explain the differences between the planted and unplanted SF wetlands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation